2017
DOI: 10.3390/ijerph14111297
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Pollution by Benzene and PM10 and Clinical Manifestations of Systemic Sclerosis: A Correlation Study

Abstract: Atmospheric air pollution has been associated with a range of adverse health effects. The environment plays a causative role in the development of Systemic Sclerosis (SSc). The aim of the present study is to explore the association between particulate (PM10) and benzene (B) exposure in Italian patients with systemic sclerosis and their clinical characteristics of the disease. A correlation study was conducted by enrolling 88 patients who suffer from SSc at the Fondazione Policlinico “A. Gemelli” in Rome (Italy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
1
15
1
3
Order By: Relevance
“…Second, our results showed that both PM10 and per capita greenhouse gas emissions were significantly negatively correlated with expected life expectancy. These findings that pollutant emissions cause negative impact on public health are similar to the results proposed by [2,46,47]. In contrast to [48], this paper does not provide empirical evidence for the conclusion that greenhouse gases have contributed to the human development index.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Second, our results showed that both PM10 and per capita greenhouse gas emissions were significantly negatively correlated with expected life expectancy. These findings that pollutant emissions cause negative impact on public health are similar to the results proposed by [2,46,47]. In contrast to [48], this paper does not provide empirical evidence for the conclusion that greenhouse gases have contributed to the human development index.…”
Section: Discussionsupporting
confidence: 79%
“…Rapid economic growth not only triggers massive use of fossil energy, but also leads to a rise of emissions of various types of pollutants [1]. Pollutant emissions caused by fossil energy consumption have been analyzed to endanger public physical and mental health [2,3], and numerous previous studies have found that such pollutant (e.g., PM10, PM2.5, and SO 2 ) can have a negative effect on public health [4,5,6]. Sharma et al [7] examined the link between air quality and public health in the Delhi region, and found that pollutant emissions were triggering an increase in diseases in industrialized economies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to microbes, exposure to diesel increased ETAR expression in the lungs of mice (45). In SSc, associations are present between the severity of interstitial lung disease (ILD) with the exposure to Benzol, which is another surrogate marker for traffic-induced air pollution (46). Here, endothelin receptor expressions are increased in the lungs (47).…”
Section: Abnormal High G Protein-coupled Receptor Antibodies and G Prmentioning
confidence: 99%
“…Their exposure takes on particular significance and importance both for the vulnerabilities of the users (i.e., patients with various pathologies, with an acute health status, with different immune responses, people with disabilities elderly, etc. ), and for the times of permanence in the hospital [29][30][31][32][33]. In all these healthcare environments for different needs, the healthcare and technical and administrative staffs, and the users (caregivers, elderly people, children, volunteers, students, visitors, outsourcing services' staffs, maintenance workers and suppliers, etc.…”
Section: Design and Management Aspects That Affect Indoor Air In Hospmentioning
confidence: 99%
“…patients with various pathologies, with an acute health status, with different immune responses, people with disabilities elderly, etc. ), and for the times of permanence in the hospital [29][30][31][32][33].…”
Section: Design and Management Aspects That Affect Indoor Air In Hospmentioning
confidence: 99%